A review of workplace deviance from the human resource development perspective. - Alias, Mazni; Mohd Rasdi, Roziah (2011)
Workplace deviance is a phenomenon that has been researched extensively from multiple disciplines. Our review found that deviance consists of constructive and destructive deviances. However, this paper will only focus on destructive deviance as these behaviours will have negative impact on individuals and organizations. The history, concept of workplace deviance, workplace deviance theories, issues of workplace deviance in Malaysia and its implications to both individual and organizations were discussed from the perspective of Human Resource Development. This review also suggests practical implications that HRD professionals can implement to assist individuals and organizations to reduce the prevalence of workplace deviance cases.